2023
DOI: 10.1007/s10754-023-09362-z
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket expenditure, need, utilisation, and private health insurance in the Australian healthcare system

Timothy Ludlow,
Jonas Fooken,
Christiern Rose
et al.

Abstract: Despite widespread public service provision, public funding, and private health insurance (PHI), 20% of all healthcare expenditure across the OECD is covered by out-of-pocket expenditure (OOPE). This creates an equity concern for the increasing number of individuals with chronic conditions and greater need, particularly if higher need coincides with lower income. Theoretically, individuals may mitigate OOPE risk by purchasing PHI, replacing variable OOPE with fixed expenditure on premiums. Furthermore, if PHI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In particular, PHI, which reduces out-of-pocket spending, is known to lead to increased healthcare utilization and greater inequality [18]. An Australian study reported similarly that PHI's reduction in reduces outof-pocket costs, leading to increased healthcare utilization [19].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…In particular, PHI, which reduces out-of-pocket spending, is known to lead to increased healthcare utilization and greater inequality [18]. An Australian study reported similarly that PHI's reduction in reduces outof-pocket costs, leading to increased healthcare utilization [19].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%